2022
DOI: 10.1111/tran.12582
|View full text |Cite
|
Sign up to set email alerts
|

Decolonial encounter with neo‐nationalism: The politics of indigeneity and land rights struggles in Okinawa

Abstract: This paper aims to make a contribution to ongoing debates in decolonial, indigenous, and island geographies through a case study of the Okinawan indigenous movement and its recent encounter with a neo-nationalist, and in effect neocolonial, movement. The Okinawan indigenous movement emerged against the backdrop of the continuing US military presence on Okinawa Island, which is the direct result of the post-war American military occupation and continues to be maintained by Japanese post-colonial policies. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Moreover, a recent wave of critical scholarship has discussed the need to ‘decolonise’ geographical knowledge (Jazeel, 2017; Naylor & Thayer, 2022; Noxolo, 2017) and mapping has been involved in this kind of epistemological critique. For instance, some scholars highlighted the struggles of ‘unceded territories’ against colonial and postcolonial naming, reclaiming the silenced indigenous knowledge that was part of those territories before the arrival of the colonisers (De Leeuw & Hunt, 2018; see also Nishiyama, 2022). As far as Latin America is concerned, several contributions incarnate this ‘ontological conflict’ at the level of cartography (Oslender, 2021), participating in larger reflections on rethinking crucial geographical concepts such as that of ‘territory’ (Colectivo de Geografía Crítica del Ecuador, 2017; Halvorsen, 2019) and visualising hitherto unspoken ‘social cartographies’ (Almeida & E., 2013).…”
Section: The Making Of ‘Latin’ America: Mapping and Geopoliticsmentioning
confidence: 99%
“…Moreover, a recent wave of critical scholarship has discussed the need to ‘decolonise’ geographical knowledge (Jazeel, 2017; Naylor & Thayer, 2022; Noxolo, 2017) and mapping has been involved in this kind of epistemological critique. For instance, some scholars highlighted the struggles of ‘unceded territories’ against colonial and postcolonial naming, reclaiming the silenced indigenous knowledge that was part of those territories before the arrival of the colonisers (De Leeuw & Hunt, 2018; see also Nishiyama, 2022). As far as Latin America is concerned, several contributions incarnate this ‘ontological conflict’ at the level of cartography (Oslender, 2021), participating in larger reflections on rethinking crucial geographical concepts such as that of ‘territory’ (Colectivo de Geografía Crítica del Ecuador, 2017; Halvorsen, 2019) and visualising hitherto unspoken ‘social cartographies’ (Almeida & E., 2013).…”
Section: The Making Of ‘Latin’ America: Mapping and Geopoliticsmentioning
confidence: 99%
“…It is especially promising, we think, to connect this theme with the decolonial and global South provocations of worlding geography in ways that challenge the elevation of English and whiteness within (and beyond) the ‘Institute of British Geographers’ (Esson et al, 2017; Jazeel, 2017; Jazeel et al, 2022; McFarlane, 2022; Müller, 2021). We welcome in the same spirit more reflections from geographers working in (and across) different national contexts around the world, including the contexts of First Nations and Indigenous struggles to decolonise (Daigle & Ramírez, 2019; Nishiyama, 2022; Woods, 2020). Another indexical example of this worlding work has been the recent upsurge of interest in Latin American geographies, exemplified by the new Research Group of the RGS and associated articles we have recently published from and about the region (e.g., Davies, 2021; De Lira, 2022; Ferretti & Viotto Pedrosa, 2018; Halvorsen, 2020; Hope, 2021; Kraftl et al, 2019; Novaes & Lamego, 2022).…”
mentioning
confidence: 98%
“… This paper acknowledges that the United Nations Human Rights Committee and Committee on the Elimination of Racial Discrimination have repeatedly indicated that the Government of Japan should recognize Ryukyuans/Okinawans as Indigenous peoples to ensure the protection of their rights (Committee on the Elimination of Racial Discrimination, 2018; Nishiyama, 2022; United Nations Human Rights Committee, 2022). At the same time, this paper also understands that the rights‐based discourse remains contested.…”
mentioning
confidence: 99%